On the measurement of the characteristic rotation decay time for a baseball - Koss, M. B.; Booth, T. M.; Sullo, K. M. (International Journal of Sports Science and Engineering, 2011)
We calculated an exponential characteristic rotation time decay, or spindown time, for a baseball to be T=7s ± 2s from a continuous sequence of a baseball initially rotating at approximately 800 rpm. We recorded this sequence using a high speed digital video camera recording at 420 fps during the apparent weightless regime which results from an aircraft flying proscribed parabolic trajectories. Thus, while the rotating baseball was essentially weightless and stationary with respect to the cabin of the aircraft, we definitively established that the rotation decay is significant over durations as short as 1.2 seconds on a baseball with a low translation velocity of less than 0.5 m/s.